2005
DOI: 10.1093/humrep/deh666
|View full text |Cite
|
Sign up to set email alerts
|

Is the CAG repeat of mitochondrial DNA polymerase gamma (POLG) associated with male infertility? A multi-centre French study

Abstract: Under our conditions, our study does not confirm any relationship between the polymorphic CAG repeat in the POLG gene and male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 13 publications
5
21
0
3
Order By: Relevance
“…Rovio et al 1999 [5], have shown the frequent (88 %) occurrence of genotype 10/10 in different ethnic group. As found by Krausz et al 2004; Aknin-Seifer et al 2005 [11,12], this study also suggested that the CAG repeat of the POLG gene does not play a significant role in men with severe male factor infertility.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Rovio et al 1999 [5], have shown the frequent (88 %) occurrence of genotype 10/10 in different ethnic group. As found by Krausz et al 2004; Aknin-Seifer et al 2005 [11,12], this study also suggested that the CAG repeat of the POLG gene does not play a significant role in men with severe male factor infertility.…”
Section: Resultssupporting
confidence: 76%
“…Expansion of CAG repeat in some genes is associated with various human pathologies. Implication of POLG CAG repeats in infertility is suggested by copious studies [6][7][8][9][10], but are debated [11][12][13][14][15]. As it is not clear whether the variable CAG genotype is one of the contributing factor for male infertility, an attempt was made to screen the CAG repeat motif of POLG gene exclusively in infertile men from two different districts of Tamil Nadu, South India.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies combined three (azoospermia, oligozoospermia and asthenozoospermia) or more subgroups of idiopathic male infertility to examine the distribution of CAG-repeat variants of the POLG gene. 12,13,15,[17][18][19] On the contrary, some studies analyzed only one subgroup or excluded some subgroups, such as Rani et al, 16 who studied only the association between the CAG-repeat variant and POLG-CAG-repeat variant and male infertility SY Liu et aloligoasthenozoospermia; Rovio et al, 9 who excluded azoospermic and severely oligozoospermic men; and this study, which only included asthenozoospermic and oligoasthenozoospermic men. All studies excluded patients with genetic causes of infertility (karyotype mutations, Kallman syndrome, Y-chromosome microdeletions and cystic fibrosis mutations) from the analysis; however, not all known genetic causes of male infertility were reported to be excluded in all studies.…”
Section: Polg-cag-repeat Variant and Male Infertility Sy Liu Et Al 302mentioning
confidence: 86%
“…The results from this study and other casecontrol studies 9,[11][12][13][15][16][17][18][19] were combined for meta-analysis. The departure from HWE for the control group in each study was assessed using a Pearson x 2 test for goodness of fit in the HWE program (http:// ihg2.helmholtz-muenchen.de/cgi-bin/hw/hwa1.pl).…”
Section: Statistical Analysis and Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation